Interkulturelle Zusammenarbeit in multinationalen Teams - Cramer, Tobias; Nový, Ivan, 1956-; Kleibl, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2007)
The overall goal of the dissertation is to understand cross-cultural cooperation in multinational teams and to find ways to help improve such ciiperation.For this, the study of matters was theoretically analysed first,secondly a model of influencing factors for successful multicultural teams was presented, and finally ,the derived hypotheses were tested in a field study.
Vedoucí práce: Ivan Nový
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2007
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2007
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations